WTO Reform Priorities post-COVID-19 - Bernard Hoekman (East Asian Economic Review (EAER), 2020)
Although the WTO has fulfilled several key tasks it was set up to do – providing periodic reviews of members' trade policies, resolving disputes, supporting negotiations – with the notable exceptions of the Trade Facilitation and Information Technology agreements, WTO members have not been able to negotiate new rules on "bread and butter" trade policies. The importance of doing so was illustrated by the COVID-19 pandemic which saw widespread uncoordinated recourse to trade policy instruments. This paper highlights four reforms that would bolster the effectiveness of the WTO as a forum for trade cooperation: (1) improving collection and reporting of information on trade-related policies; (2) supporting analysis-informed deliberation to establish a common understanding of the need and scope for cooperation in specific policy areas; (3) putting in place a stronger multilateral governance framework for plurilateral cooperation between groups of WTO members; and (4) reestablishing an effective dispute settlement system.
Keywords: F02; F13; F55; 330; WTO Reform; Trade Cooperation; Transparency; Plurilateral Agreements; Dispute Settlement